Pengkajian Investasi Kebun Karet Plasma = A Study on Investment of The Small Holding Rubber Farms - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
The objective of this study is to evaluate the NES (Nucleus Estate and Small Holder) Project of Talang Jaya Project, South Sumatera. Purposive sampling technique and systematic random sampling were used to get three villages and 60 sample farmers, respectively. The results showed that the NPV is Rp 5,691 thousands, IRR is 22.6%, Net BCR is 2.83, and DPP (Discounted Payback Period) is 10 years at the average production level of 1308 kg/ha/year and average price of Rp 640 per kg. A sensitivity analysis showed that at a lower price level and lower production level they are Rp 2,066 thousands, 16.4%, 1.67 and 13 years, respectively. The higher is the price level the higher is the farmers' benefit. An economic analysis of 20 yeark showed that this project is still feasible, and in 15 years is also still feasible at a low level. At the average production level and the average price level an investment loan can be repaid at a period of 22 years. A sensitivity analysis showed that tha credit cannot be repaid in 30 years at lower price level at all production levels. At the average price level the credit can be repaid at the average production level in 22 years, and at high production level in 20 years. If the price is higher the loan can be repaid in 19, 18, and 16 years at the low, the average, and the high production levels, respectively.